1998
DOI: 10.1111/j.1600-0676.1998.tb00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term effects of transjugular intrahepatic portosystemic shunt (TIPS) on functional liver plasma flow in patients with advanced cirrhosis

Abstract: — Aims/Background: TIPS, an effective procedure applied for the treatment of complications of portal hypertension, is potentially followed by worsening of the hyperdynamic circulation of cirrhosis and the impairment of liver function. The aim of the present study was to evaluate short‐term changes of functional liver plasma flow after application of TIPS, using the hepatic (extrarenal) clearance of D‐sorbitol (S‐HCl). Methods: Twenty‐five cirrhotic patients submitted to TIPS for prevention of variceal rebleedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…There has not been a consensus on the effects of TIPS on hepatic function from decreasing the portal blood pressure and the portal blood flow. There are reports that TIPS does not change [29][30][31][32] or that it worsens 33,34 the liver function, but there is no report stating that TIPS improves the liver function. In studies on a hepatic cellular level, TIPS was reported to decrease ICGCli.…”
Section: Discussionmentioning
confidence: 99%
“…There has not been a consensus on the effects of TIPS on hepatic function from decreasing the portal blood pressure and the portal blood flow. There are reports that TIPS does not change [29][30][31][32] or that it worsens 33,34 the liver function, but there is no report stating that TIPS improves the liver function. In studies on a hepatic cellular level, TIPS was reported to decrease ICGCli.…”
Section: Discussionmentioning
confidence: 99%